WILSON'S DISEASE (A report of two cases) - KANITKAR, M (Med J Armed Forces India, 1994)
Two cases of Wilson's disease are reported. First case presented with fulminant hepatic failure and had a fatal outcome. The second had an insiduous onset, neurological manifestations, and is progressing satisfactorily on zinc therapy. Problems in diagnosis and treatment are highlighted.